The Development of Robot Control, Robot Simulation and Digital Image Processing - Viera Poppeova; Juraj Uricek; Robert Zahoransky; Tibor Galbavy; Klaus Muller; Swen Schmeisser (Communications - Scientific letters of the University of Zilina, 2005)
The automation of manufacturing processes finds its application almost in all spheres of the economy of all industrial developed countries. Its inseparable part is represented by robotisation of manufacturing technologies in production. Nowadays robots and manipulators are quite common building element of automated workplaces, where they safeguard namely manipulation, control and measurement operations, operation and manipulation transport, exchange of tools, removing scraps in production. They are the only real tools for performing operations in dangerous or harmful environment for people (welding, spraying of colour or anticorrosive paint, work with radioactive material, etc.).Robots are introduced in industrial enterprises at present to allow control of six axes, they are capable to work in learning regime, have sufficient capacity of the control system memory also for a complicated manipulation. They are able to adapt to changing conditions of performance while preserving the required quality based on sensor information about the inner state of the robot as well as about outside robot environment. They have automated exchange of effectors, point or curve movement control (or combined), possibility of connection of their own control system with the host computer, etc.